Breastfeeding and the anthropometric profile of children with sickle cell anemia receiving follow-up in a newborn screening reference service - Nogueira,Zeni Drubi (2015)
OBJECTIVE: To study the breastfeeding history (BF) and the anthropometric status of children with Sickle Cell Disease (SCD). METHODS: A cross-sectional study of 357 children with SCD aged between 2 and 6 years, regularly followed at a Newborn Screening Reference Service (NSRS) between November 2007 and January 2009. The outcome was anthropometric status and the exposures were: BF pattern, type of hemoglobinopathy and child's age and gender. RESULTS: The mean (SD) age was 3.7 (1.1) years, 52.9% were boys and 53.5% had SCA (hemoglobin SS). The prevalence of exclusive breastfeeding (EBR) up to six months of age was 31.5%, the median EBR times (p25-p75) was 90.0 (24.0-180.0) days and the median weaning ages (p25-p75) was 360.0 (90.0-720.0) days respectively. Normal W/H children experienced EBR for a mean duration almost four times longer than malnourished children (p=0.01), and were weaned later (p<0.05). Height deficit was found in 5.0% of children, while all the children with severe short stature had had SCA (hemoglobin SS) and were older than 4 years of age. CONCLUSIONS: EBF time and weaning age were greater than that found in the literature, which is a possible effect of the multidisciplinary follow-up. Duration of EBF and later weaning were associated with improved anthropometric indicators.